Multidimensional Analysis of Well-Being Domains in Japan: Fulfillment, Importance, and Contribution to Overall Well-Being - Yasuyuki Kudo; Tobu Tomabechi; Yuho Shimizu; Shuhei Fukuyama; Yuki Igeta; Mizuka Ohtaka; Takaaki Hashimoto; Kaori Karasawa (Urban Science)
Efforts to measure citizen Well-Being (WB) and integrate the results into policymaking have gained momentum globally. In this study, we evaluate the domains comprising WB indicators based on three dimensions—fulfillment, importance, and contribution to overall WB—to effectively apply these findings to policies and urban development strategies. An online survey of 1394 Japanese adults (630 women, 764 men) was conducted to analyze the rankings of the 24 domains (comprising 46 items) of the Liveable Well-being City indicator, a widely used framework in Japan, across these three dimensions. The analysis revealed that items in domains related to Life Environment ranked highest regarding fulfillment, whereas domains related to Living Authentically or Life Environment ranked highest in importance. Meanwhile, items in the domains associated with Community Relationships or Living Authentically tended to rank higher in contribution to overall WB; however, this was not statistically significant. These results suggest inconsistencies in evaluation across dimensions and highlight the necessity of incorporating three-dimensional evaluations into policymaking and policy improvement. Furthermore, the findings indicate that strategies targeting Community Relationships could be particularly effective in enhancing WB and providing actionable policy design and implementation guidance.